Factors that influencing the customer decision to purchase Islamic banking products - Surjaatmadja, Surachman; Saputra, Jumadil (Opción, 2020)
This study aims to determine the factors that influence the decision to purchase or intention to use Islamic banking service products in Indonesia. The design of this study is a quantitative approach. For analyzing the multiple relationships, we use Linear Structural Relations (LISREL version 8.0). The results of this study indicate that the customer's decision or intention to use Islamic Bank product services is influenced by the perception of product diversity with a contribution of 21%. In conclusion, attention dimension contributes 95% to marketing communications carried out by Islamic Banks in Indonesia.